2005
DOI: 10.1246/cl.2005.1364
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polycrystalline Spherical SnO2 Microparticles via Hydrothermal Treatment in the Presence of Mixed Surfactants

Abstract: The spherical microparticles of SnO2 were synthesized successfully by hydrothermal treatment of their precursor consisting of SnCl4 and mixed surfactants, followed by calcination at 500 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Previously, various types of SnO 2 particles have been prepared by the hydrothermal process in the presence of organic molecules, where the hydrothermal conditions accelerate the dissolution and precipitation and the organic molecules controls the nucleation and growth. [15][16][17][18][19][20] Guo et al prepared nanorods consisting of SnO 2 crystallites using cetyltrimethyl ammonium bromide (CTAB) as a template. 15 Du et al reported the formation of SnO 2 hollow microspheres composed of nanoparticles from a precursor solution containing carbamide.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, various types of SnO 2 particles have been prepared by the hydrothermal process in the presence of organic molecules, where the hydrothermal conditions accelerate the dissolution and precipitation and the organic molecules controls the nucleation and growth. [15][16][17][18][19][20] Guo et al prepared nanorods consisting of SnO 2 crystallites using cetyltrimethyl ammonium bromide (CTAB) as a template. 15 Du et al reported the formation of SnO 2 hollow microspheres composed of nanoparticles from a precursor solution containing carbamide.…”
Section: Introductionmentioning
confidence: 99%
“…Lupan et al [26,27] have reported the preparation of SnO 2 microcubes and nanowires by a simple hydrothermal process at low temperatures below 98 1C without the use of templates or seed crystals. Moreover, organic additives play an important role for the morphological control of SnO 2 crystals via hydrothermal processes [28][29][30][31][32][33][34]. Guo et al [28] prepared nanorods consisting of SnO 2 crystallites using cetyltrimethyl ammonium bromide (CTAB) as a template.…”
Section: Introductionmentioning
confidence: 99%